Correlation of inflammatory mediators in prostatic secretion with chronic prostatitis and chronic pelvic pain syndrome. (1st August 2017) - Huang, T. R.; Li, W.; Peng, B.
Summary: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common clinical syndrome, and the mechanisms underlying the relationship between CP/CPPS and ED are still unclear. This study aimed to investigate the differential expression of 40 inflammatory mediators in patients with CP/CPPS and to demonstrate whether these mediators related to the severity of erectile function. Eighty cases of patients with CP/CPPS were selected, including 40 cases of IIIA and 40 cases of IIIB, with 20 cases of healthy men as controls. After collecting their expressed prostatic secretion, cytokines levels in EPS were determined by ELISA using ELISA kits. The IIEF‐5 questionnaire was used to evaluate erectile function. IIEF‐5 scores were significantly lower in the IIIA and IIIB groups than those in the control group. The expression of IL‐8, IL‐1β and ICAM‐1 was markedly higher in the IIIA and IIIB groups than in the control group. The expression of IL‐8, IL‐1β and ICAM‐1 in the IIIA group was higher than that in the IIIB group. The expression of IL‐8, IL‐1β and ICAM‐1 was negatively correlated with IIEF‐5 scores in both IIIA and IIIB patients. In conclusion, IL‐8, IL‐1β and ICAM‐1 are possible indicators for the clinical diagnosis of CP/CPPS and evaluation of erectile function on patients with CP/CPPS.